Non-linear numerical analysis of plywood board timber connections by DOE-FEM and full-scale experimental validation - DEL COZ DIAZ, J. J; GARCIA NIETO, P. J; MARTINEZ-LUENGAS, A. Lozano; DOMINGUEZ, F. J. Suarez; HERNANDEZ, J. Domínguez (Engineering structures, 2013)
[Display omitted] ► Plywood board timber connections are not investigated. ► The performance of a new wood–wood connection is calculated by means of numerical methods and experimental validation. ► The experimental results show good agreement. The aim of this work is the non-linear study by the finite element method (FEM) of the mechanical performance of timber joints’ systems for the beam elements used in the construction of roofs, whenever they are bent at the same plane. A full three-dimensional numerical analysis was carried out assuming an orthotropic behavior model of the material with a failure criterion based on the requirements of the Eurocode 5 rule. The non-linearity is due to the contact between the joint’s bolts and the wood’s elements and plywood’s elements as well as the large displacements in the system. The study also includes the full-scale experimental test of six entire trusses of 6m span and 1.0m high, subject to bending in four points according to the procedure established in the UNE-EN 595:1996 rule. Three specimens have the connection object of this study while the other three remaining ones have the steel fitting used regularly in these wood structures. The purpose of this work is to replace the joint pieces used regularly up to now, built with steel fitting, with other pieces made with wood’s sections obtained from birch plywood board. This aim is achieved comparing the resistant characteristics of both connection methods and validating the developed numerical model. In order to know the influence of the most important variables in the structural behavior of the plywood board timber connection, a design of experiments (DOEs) is carried out. Finally, the more meaningful conclusions from the models and analyses carried out are exposed, showing a good agreement between the numerical results and experimental tests, as well as a very similar performance between the connection systems analyzed: steel fittings and birch plywood board.